2018
DOI: 10.1002/cbic.201700616
|View full text |Cite
|
Sign up to set email alerts
|

Heat Shock Proteins Revisited: Using a Mutasynthetically Generated Reblastatin Library to Compare the Inhibition of Human and Leishmania Hsp90s

Abstract: Thirteen new reblastatin derivatives, with alkynyl, amino and fluoro substituents on the aromatic ring, were prepared by a chemo-biosynthetic approach using an AHBA(-) mutant strain of Streptomyces hygroscopicus, the geldanamycin producer. The inhibitory potencies of these mutaproducts and of an extended library of natural products and derivatives were probed with purified heat shock proteins (Hsps), obtained from Leishmania braziliensis (LbHsp90) as well as from human sources (HsHsp90). We determined the acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 48 publications
(28 reference statements)
0
13
0
Order By: Relevance
“…Reinforcing our results, some derivatives of reblastatin, a GA-related compound, were recently shown to exhibit increased binding to L . braziliensis Hsp83 than to human Hsp90 23 . Similarly, Kanwar et al .…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Reinforcing our results, some derivatives of reblastatin, a GA-related compound, were recently shown to exhibit increased binding to L . braziliensis Hsp83 than to human Hsp90 23 . Similarly, Kanwar et al .…”
Section: Discussionmentioning
confidence: 86%
“…Recently, derivatives of reblastatin, a GA-related compound, have been shown to bind to L . braziliensis Hsp83 and exert inhibitory activity over this protein 23 . Treatment with 17-AAG was further shown to reduce the percentage of macrophages infected by L .…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that co-chaperones of Hsp90 may augment parasite drug resistance, and such a phenomenon would further justify the importance of combinational therapies against parasitic infections. Leishmania braziliensis Hsp90 (LbHsp90) was shown to be selectively targeted by alkynyl substituents of reblastatin (Figure 2) obtained from Streptomyces hygroscopicus (GA producer) [79]. Thus, identification of species-specific Hsp90 inhibitors remains a promising agenda.…”
Section: Hsp90 Familymentioning
confidence: 99%
“…We recently reported that the position of the fluorescence label attached to ATP can influence the binding to Hsps. 25 With respect to sterically congested gambogic acid (1), one may consider uncompetitive effects instead. Therefore, we included a modified orthogonal assay in our studies.…”
Section: ■ Conformation Of Gba-binding By Mstmentioning
confidence: 99%
“…The studies revealed that different Hsps have different susceptibilities to the test compounds. 22,25 Surprisingly, ATP displacement was also induced by gambogic acid (1), which supposedly binds outside the ATP-binding pocket (Figure S3). In addition, orthogonal MST experiments revealed that ATP is required for the binding of 1.…”
Section: ■ Conclusionmentioning
confidence: 99%